1957
DOI: 10.1017/s0022149x00033241
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Larval Stages of Muellerius capillaris within the Intermediate Hosts Agriolimax agrestis and A. reticulatus

Abstract: 1. The rate of development of the larvae of M. capillaris is slowed down as the temperature is lowered; at 25°C. the infective stage is reached after 8 days; at 5°C. after 98 days.2. The differences between “pre-infective” and “infective” larvae, as described by Gerichter (1948), have been confirmed.3. Larvae at the “infective” stage can withstand artificial digestion, but “pre-infective” larvae are unable to do so.4. The infective larvae can survive for long periods within the foot of the intermediate host.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2
2

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
4
24
2
2
Order By: Relevance
“…However, in our experi ment, the values for number and percentage of L-III per mollusc were lower than those cited by Sauerländer (1979) for both parameters and by Zdzitowiecki (1976) for the former. If the time needed by the M. capillaris larvae to reach the third stage in C. nemoralis is considered (Table II), it seems that higher temperatures induce faster development, and this agrees with the observations of Rose (1957) and Ryšavy (1969).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, in our experi ment, the values for number and percentage of L-III per mollusc were lower than those cited by Sauerländer (1979) for both parameters and by Zdzitowiecki (1976) for the former. If the time needed by the M. capillaris larvae to reach the third stage in C. nemoralis is considered (Table II), it seems that higher temperatures induce faster development, and this agrees with the observations of Rose (1957) and Ryšavy (1969).…”
Section: Discussionsupporting
confidence: 77%
“…was similar to that indicated by Rehnova (1955), Soltys (1964), Morrondo et al (1980), Morrondo and Manga (1982) and Reguera (1983). However, this period was shorter than that observed by Gerichter (1951) in his study and longer than that quoted by Pavlov (1937), Williams (1942) and Rose (1957).…”
Section: Discussioncontrasting
confidence: 49%
“…All larvae were examined and quantified at X100-X400, and larval stages determined using morphological criteria established for U. pallikuukensis (Kutz, Hoberg et al, 2001). The LI, L2, and early L3 (dead and live early L3, which had poor motility and survival in digest fluid) were considered preinfective larvae, whereas intermediate L3 (partially ensheathed in the L2 cuticle) and late L3 (exsheathed) were considered infective larvae (as defined by Gerichter, 1948;Rose, 1957;Platt, 1978 (Table I). Deroceras laeve were obtained from protostrongylid-free laboratory colonies and Catinella sp.…”
Section: Native Intermediate Hostsmentioning
confidence: 99%
“…In a third muskox we have demonstrated that L3 which had emerged from live D. reticulatum are also infective. Larval emergence from gastropods has been reported for the protostrongylids P. stilesi, M. capillaris, and C. ocreatus and for Angiostrongylus costaricensis (Davtyan 1950, cited in Boev 1975Rose 1957;Monson and Post 1972;Ubelaker et al 1980). Larval emergence has also been reported for Protostrongylus boughtoni in snowshoe hares, and although the emerged L3 are infective for domestic rabbits, they are considered an unlikely source of infection for the natural definitive hosts (Kralka and Samuel 1984).…”
Section: Host-parasite Biologymentioning
confidence: 98%